Digitalization opportunities for the procurement function: pathways to maturity. Issue 11 (5th November 2020) - Seyedghorban, Zahra; Samson, Danny; Tahernejad, Hossein
Abstract : Purpose: This research aims at investigating the common practical problem of how procurement can be transformed from tactical and administrative to becoming an organizational strategic partner and indeed a competitive weapon, using modern technologies in particular. We investigated how procurement can be reinvented, from being digitized to digitalized to digitally integrated, ultimately contributing in business terms beyond supply chain effectiveness but also to profit generation. Design/methodology/approach: A case study approach was designed to investigate three firms, each at very different stages of digital maturity in procurement. Interviews with managers, investigation of processes and documentary materials and in-depth follow-up discussions were conducted. Findings: The iterative digitalization transformation discovered encompasses complexities rooted in organizational structure, supply chain design and the management of the technology for employees' uptake. There are both operations and strategy implications as a result. This initial research phase led to mapping a model of digital maturity as well as identifying its underlying constructs. Originality/value: This research discovered that the implementation of digital technologies can lead the procurement function of the supply chain to completely grow out of its administrative and clerical shell into a strategic, consultative, value-adding and potentially revenue-generating function, thereby contributing to the well-being of not only the supply chain but also the entire organization.